2016
DOI: 10.1136/archdischild-2016-311639
|View full text |Cite
|
Sign up to set email alerts
|

Infantile wheeze: rethinking dogma

Abstract: Wheeze is a common symptom in young children and is usually associated with viral illnesses. It is a major source of morbidity and is responsible for a high consumption of healthcare and economic resources worldwide. A few children have a condition resembling classical asthma. Rarer specific conditions may have a wheezy component and should be considered in the differential diagnosis. Over the last half century, there have been many circular discussions about the best way of managing preschool wheeze. In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
0
11
0
9
Order By: Relevance
“…Some of the differences can be explained by variations in the definitions for breastfeeding exclusivity and duration, and methods to diagnose asthma in children [ 87 ]. It is known that many infants who wheeze in the first years of life do not develop asthma in later life [ 88 ], but wheeze is often used as the diagnostic marker of asthma. There are several notable large prospective birth cohorts, such as Avon Longitudinal Study of Parents and Children (ALSPAC) [ 50 ], Prevention and Incidence of Asthma and Mite Allergy (PIAMA) [ 89 ] and the cross-sectional International Study of Asthma and Allergies in Childhood (ISAAC) [ 90 ] study, with data from these studies considered of higher quality [ 75 ].…”
Section: Breastfeeding and Immunological Outcomesmentioning
confidence: 99%
“…Some of the differences can be explained by variations in the definitions for breastfeeding exclusivity and duration, and methods to diagnose asthma in children [ 87 ]. It is known that many infants who wheeze in the first years of life do not develop asthma in later life [ 88 ], but wheeze is often used as the diagnostic marker of asthma. There are several notable large prospective birth cohorts, such as Avon Longitudinal Study of Parents and Children (ALSPAC) [ 50 ], Prevention and Incidence of Asthma and Mite Allergy (PIAMA) [ 89 ] and the cross-sectional International Study of Asthma and Allergies in Childhood (ISAAC) [ 90 ] study, with data from these studies considered of higher quality [ 75 ].…”
Section: Breastfeeding and Immunological Outcomesmentioning
confidence: 99%
“…Many studies do not measure lung function and must rely on parent-reported or self-reported asthma symptoms or medication use. This is problematic because wheezing is often used as the diagnostic marker of asthma, yet wheezing can be caused by infections that are unrelated to asthma, and not all infants or children who wheeze proceed to develop asthma [ 41 ]. In addition, different asthma phenotypes exist, such as atopic or non-atopic asthma, and early- or late-onset asthma [ 42 , 43 ].…”
Section: Breastfeeding and Asthma: What Is The Evidence And Why Imentioning
confidence: 99%
“…It has been demonstrated that many “early wheezers” do not subsequently develop persistent asthma . There may even be an inverse relationship between early infection‐induced wheeze and subsequent asthma . It should be noted that most of the studies assessing asthma included in this systematic review were realistically measuring wheeze rather than asthma, as age at health outcome assessment does not allow for appropriate asthma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…42 There may even be an inverse relationship between early infection-induced wheeze and subsequent asthma. 67 It should be noted that most of the studies assessing asthma included in this systematic review were realistically measuring wheeze rather…”
Section: Discussionmentioning
confidence: 99%